Toward a Theory of International Currency - Kiminori Matsuyama (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1991)
Our goal is to provide a theoretical framework in which both positive and negative aspects of international currency can be addressed in a systematic way. To this end, we use the framework of random matching games and develop a two country model of the world economy, in which two national fiat currencies compete and may be circulated as media of exchange. There are multiple equilibrium which differ in the areas of circulation of the two currencies. In one equilibrium, the two national currencies are circulated only locally. In another, one of the national currencies is circulated as an international currency. There is also an equilibrium in which both currencies are accepted internationally. We also find an equilibrium in which the two currencies are directly exchanged. The existence conditions of these equilibria are characterized, using the relative country size and the degree of economic integration as the key parameters. In order to generate sharper predictions in he presence of multiple equilibria, we discuss an evolutionary approach to equilibrium selection, which is used to explain the evolution of the international currency as the two economies become more integrated. Some welfare implications are also discussed. For example, a country can improve its national welfare by letting its own currency circulated internationally, provided the domestic circulation is controlled for. When the total supply is fixed, however, a resulting currency shortage may reduce the national welfare.
Keywords: 330; Best Response Dynamics; Evolution of International Currency; Money as a Medium of Exchange; Multiple Currencies; (Nonuniform) Random Matching Games